Peningkatan Pemahaman Konsep dan Kemampuan Pemecahan Masalah Logaritma melalui Penerapan PBL Berbasis Keagamaan: Penelitian - Khairi, Ahmad Khotibul Umam; Hidayah, Shofia; Musthofa, Musthofa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This classroom action research (CAR) investigates the efficacy of implementing the modified Problem Based Learning (PBL) model, synchronized with intrinsic religious values, aiming to enhance students’ essential conceptual mastery and complex problem-solving skills in the Logarithm subject matter. The study involved 24 students from the X-Grade Religious Specialization Class at MA Nurul Jadid. This intervention was urgently initiated due to a severe empirical gap, where the pre-cycle assessment revealed a 0% classical learning completeness rate, a failure primarily induced by conceptual misunderstandings, persistent procedural difficulties, and consequential operational carelessness. The PBL methodological solution was executed through a spiral-reflective approach across three distinct cycles, with specific actions focusing on authentic problem inquiry, deeply supported by the internalization of systematic thinking and responsibility attitudes derived from a religious perspective. Quantitative findings emphatically revealed a progressive and substantial increase in student achievement: 0% in the Pre-Cycle, steadily increasing to 25% in Cycle I, 46% in Cycle II, and ultimately reaching the optimal target of 83% in Cycle III. The most substantial leap (37%) was recorded in Cycle III, following interventions specifically targeting the affective domain, which successfully mitigated non-cognitive errors by instilling the moral responsibility for result verification. The definitive conclusion affirms that the Modified PBL Model based on Religious Context serves as a proven, highly effective, and comprehensive strategy to overcome Logarithm learning difficulties and holistically satisfy the mandated classical success criteria.